ENDOTHELIAL DYSFUNCTION AND HEMOSTASIS SYSTEM IN PATIENTS AT RISK FOR OBSTETRIC PATHOLOGY. SYSTEMIC APPROACH TO DIAGNOSIS AND THERAPY - E. M. Jobava; K. R. Nekrasova; D. P. Artisanova; L. A. Heidar; G. Yu. Sudakova; S. G. Danelyan; D. V. Blinov; Yu. E. Dobrokhotova (IRBIS LLC, 2016)
This article describes the features of the hemostatic system and endothelial function in pregnant patients who are at risk for obstetric complications: chronic hypertension, type 1 diabetes, gestational diabetes mellitus, epilepsy, a pathology of leg veins, miscarriage. Based on this study developed an algorithm for diagnosis of endothelial dysfunctionand pathology of the hemostatic system in these patients. Given the major pathogenetic aspects, provides detailed pharmacotherapy revealed pathology. Developed a scale of «the assessment of the thrombophilia and methods of its correction during pregnancy and on the background of extragenital pathology®», which allows you to identify and find adifferentiated pharmacotherapy with certain dosage, duration of the course in the dynamics and control, regardless of the methods and standards of determining the parameters of hemostasis.